DEA Model for Considering Relationship between Supply Chain Members - Patitad, Patchanee; Watanabe, Woramol Chaowarat (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 4 (2022): October-December 2022, 2022)
Background:   A supply chain is a network system that consists of many key players from initial production to fulfilling customers ’ requirements . The performance of a supply chain can be measured by some variations of Network Data Envelopment Analysis ( network DEA ) which is a technique to measure the relative efficiency of a system, considering its internal structure. However, most variations of the network DEAs are not designed to include consideration of contract terms . Manufacturers often have contracts with suppliers for the long - term supply of their product . Such contracts are not easily terminated, modified or replaced . Alternative types of contracts, that do not bind the manufacturer to long - term commitments, can be quickly replaced by the manufacturer and / or supplier, to improve their supply chain performance . Therefore, the type of contracts that are extant or being considered is an important consideration when analyzing supply - chain performance . In this paper, a new network DEA, which can evaluate the efficiency of supply chains by considering the contract status, is proposed . Methods:  By including the contract type in the DEA model in the representation of the internal structure of the supply chain, the efficiency of replaceable supplier contracts is acknowledged in the proposed methodology . This factor then contributes to the calculated efficiency score for the supply chain by comparing it with virtual chains that have the most efficient production capabilities . A virtual chain is generated by replacing an inefficient member with a more efficient one . To show the effectiveness and applicability of the proposed model, a case study of Thailand ’ s processed food industry is used . Results:   The results show that using the proposed model can identify inefficiencies in the supply chains by considering actual contract situations . It also can provide alternative instances of inefficient supply chains to help to achieve an efficient situation .   Conclusions:   The proposed model allows us to consider the efficiency of supply chains that include changeable suppliers who are themselves efficient . The case study used in the study was a processed food supply chain in Thailand . The results of the case study show that the proposed model can help assessors to understand their supply chain efficiency and also the effects of their suppliers' efficiency . Keywords: Data Envelopment Analysis (DEA); Supply Chain; Food Industry